2015
DOI: 10.1002/2014ja020703
|View full text |Cite
|
Sign up to set email alerts
|

Control of the topside Martian ionosphere by crustal magnetic fields

Abstract: Sounding (MARSIS) instrument onboard Mars Express of the thermal electron plasma density of the Martian ionosphere and investigate the extent to which it is influenced by the presence of Mars's remnant crustal magnetic fields. We use locally measured electron densities, derived when MARSIS is operating in active ionospheric sounding (AIS) mode, covering an altitude range from ∼300 km to ∼1200 km. We compare these measured densities to an empirical model of the dayside ionospheric plasma density in this diffusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
59
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 57 publications
(70 citation statements)
references
References 56 publications
11
59
0
Order By: Relevance
“…The electron densities at an altitude of 325 km are by a factor of about 2 larger in areas of strong crustal magnetic fields than in areas of weak crustal magnetic fields. This is consistent with the results obtained by Andrews et al [, ] who used local electron density measurements at altitudes higher than about 300 km. As for the effect of the magnetic field inclination, there is likely an interplay between the vertical and horizontal transport [ Andrews et al , ; Matta et al , ].…”
Section: Discussionsupporting
confidence: 93%
“…The electron densities at an altitude of 325 km are by a factor of about 2 larger in areas of strong crustal magnetic fields than in areas of weak crustal magnetic fields. This is consistent with the results obtained by Andrews et al [, ] who used local electron density measurements at altitudes higher than about 300 km. As for the effect of the magnetic field inclination, there is likely an interplay between the vertical and horizontal transport [ Andrews et al , ; Matta et al , ].…”
Section: Discussionsupporting
confidence: 93%
“…At higher altitudes, electron densities are below the lower detection threshold of the MARSIS radar sounding. Further, electron densities at altitudes higher than about 325 km generally follow a simple exponential decrease with the altitude (e.g., Duru et al, , ), which has been statistically well mapped using the MARSIS locally evaluated electron densities (Andrews et al, ; Němec et al, ). In the present study, LPW electron density measurements are important for the two main reasons: (i) Due to the lower perigee of MAVEN as compared to Mars Express, they allow us to fill the altitudinal gap between the MARSIS radar sounding and MARSIS locally evaluated electron densities, and (ii) at lower altitudes, one can compare LPW in situ measurements with electron density profiles obtained by the MARSIS radar sounding.…”
Section: Data Setmentioning
confidence: 97%
“…Following former statistical results on electron density profile shapes (Němec et al, ), they suggested to use an empirical shape composed of a smooth transition between two exponential dependencies with different scale heights, with the scale height H 2 at higher altitudes being larger than the scale height H 1 at lower altitudes (Gurnett et al, ; Morgan et al, ): lnne=C+θ1+θ22(zz0)+θ2θ12(zz0)2+δ24 where θ 1 =1/ H 1 , θ 2 =1/ H 2 , z 0 is a transition altitude corresponding to the altitude where the two asymptotic dependencies intersect, δ is a quantity proportional to the radius of curvature, and C is a constant. The value of θ 2 can be adopted from statistical models of electron density scale height at high altitudes (Andrews et al, ; Němec et al, ). For given values of z 0 and δ , the values of C and θ 1 are then unambiguously given by the conditions that (i) the electron density at the spacecraft altitude must be equal to the one actually measured, and (ii) the measured time delay at the lowest frequency available from the ionospheric sounding must be equal to the time delay calculated using the empirical electron density profile.…”
Section: Empirical Dependence In the Transition Regionmentioning
confidence: 99%
“…The lifetime of these features was about 10 days. They could be ice particles reflecting sunlight, or related to a solar wind event, however, until now, no clear explanation has been given to explain these observations, although it is interesting to note that this period was characterized by an active solar period, during which coronal mass ejections hit Mars (Andrews et al 2015).…”
Section: Additional Observations and Concluding Commentsmentioning
confidence: 99%
“…Elevated ionospheric densities and localized spatial structures are seen above magnetic anomalies (Andrews et al 2014(Andrews et al , 2015Matta et al 2015;Ma et al 2014;Dubinin et al 2012;Safaeinili et al 2007), and can be explained to first order by a larger ionization due to higher energetic particle fluxes spiraling along the magnetic field lines (Lillis and Fang 2015).…”
Section: Variability Of the Upper Atmospherementioning
confidence: 99%